Well-Posedness of the Cauchy Problem for Hyperbolic Equations with Non-Lipschitz Coefficients - Akbar B. Aliev; Gulnara D. Shukurova (Abstract and Applied Analysis)
We consider hyperbolic equations with anisotropic elliptic part and some non-Lipschitz coefficients. We prove well-posedness of the corresponding Cauchy problem in some functional spaces. These functional spaces have finite smoothness with respect to variables corresponding to regular coefficients and infinite smoothness with respect to variables corresponding to singular coefficients.